Nitrogen-doped graphene-based metal composites for the non-enzymatic detection of hydrogen peroxide / Mohammad Taghi Tajabadi Poor - Mohammad Taghi , Tajabadi Poor (2020)
Recently, much attention has been devoted to detecting hydrogen peroxide (H2O2) because of its extensive range of applications in chemical synthesis, the textile industry, food production, fuel cell devices, and even in many oxidative biological reactions. Among the various methods of detection of H2O2, electrochemical sensors has many advantages, such as simplicity, high efficiency and sensitivity, as well as good selectivity., To improve the sensitivity of non-enzymatic sensors, noble metal nanoparticles with particular electrocatalytic activities can be utilized. The present research is aimed to design a hybrid approach for the development of novel nanostructures for non-enzymatic detection of H2O2. Herein, the electrochemical measurements were performed using a potentiostat/galvanostat. A X-ray powder diffractometer (XRD), transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM) were utilized to investigate the phase structure and composition, as well as morphology and particle size of the electrodes. In addition, Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) were also utilized to further investigate the structural and electronic properties and to identify the nitrogen-bonded groups in the as-synthesized nitrogen doped graphene (NG), respectively. For this purpose, NG was initially prepared using a microwave-assisted method that comprises of a three-step process of graphite oxidation, exfoliation, and chemical reduction using a reducing agent at low temperature. In the first step, NG was electrophoretically deposited (EPD) on an indium tin oxide (ITO) electrode, following by silver nanodendrites (AgNDs) and platinum nanoflowers (PtNFs) as the subsequent layers via electrochemical deposition. The as-prepared AgNDs/NG-modified ITO electrode was used as a non-enzymatic H2O2 sensor and exhibited high stability, outstanding reproducibility and good electrocatalytic activity for the quick detection of H2O2 over a wide linear range from 100 μM to 80 mM. In the second case, PtNFs/Ngmodified ITO electrode with different NG loadings were utilized as non-enzymatic H2O2 sensors, where ITO modified with 0.05 mg ml−1 NG loading exhibited improved properties for H2O2 detection over a linear range from 1 μM to 1 mM.